Managing Sustainable Professional Development for Madrasah Teachers: Enhancing Scientific Publications - Mardia, Mardia; Rahmawati, Rahmawati; Muin, Suhailah Abdul; Ramli, Nurleli (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Scientific publication activities are generally not the primary assessment of teacher performance in madrasahs, but scientific publications can impact teacher professionalism and the madrasah's reputation. This study aims to analyse the strategic management of sustainable professional development (SPD) among madrasah teachers in Islamic boarding schools (pesantren) as a solution to improving their scientific publication capacity. This study employed a qualitative approach, utilising a case study design. Data were collected through observations and semi-structured interviews with 20 madrasah teachers. Data were analysed using the Miles & Huberman interactive data analysis model. The findings suggest that a structured managerial approach, combined with capacity-building interventions and suitable institutional support, can substantially enhance teachers' productivity in scientific publications. This research has implications for improving teacher pedagogical quality, particularly in terms of delivering learning materials that align with scientific developments. It also serves as a consideration for cross-sector collaboration between Islamic boarding schools, madrasahs, and educational institutions to contribute to overcoming structural challenges and encouraging teachers' continuous professional development.